2020
DOI: 10.1016/j.cstp.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Trains, Twitter and the social licence to operate: An analysis of Twitter use by train operating companies in the United Kingdom

Abstract: WestminsterResearch http://www.westminster.ac.uk/westminsterresearch Trains, Twitter and the social license to operate: A case study analysis of Twitter use by train operating companies in the United Kingdom Howard, J. M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In their study, in Greece, 64% of participants (mostly young and in higher education) receive travel information via social networks. Twitter, especially, is frequently used by transport operators to disseminate public RTI [35,36]. However, this type of source raises issues of intergenerational and social equity as it has been shown that social network users are not representative of the general public [37] since they are younger and more educated.…”
Section: Traveller Information Usage Under Normal Conditionsmentioning
confidence: 99%
“…In their study, in Greece, 64% of participants (mostly young and in higher education) receive travel information via social networks. Twitter, especially, is frequently used by transport operators to disseminate public RTI [35,36]. However, this type of source raises issues of intergenerational and social equity as it has been shown that social network users are not representative of the general public [37] since they are younger and more educated.…”
Section: Traveller Information Usage Under Normal Conditionsmentioning
confidence: 99%
“…Meanwhile, for an established project, ongoing communication, providing avenues for community members to make their issues related to the company known and responding to those problems in a meaningful way are all key strategies for maintaining social license (Baines & Edwards, 2018). Additionally, using social media to interact with stakeholders and provide helpful information can be important in supporting social license (Howard, 2020). Consistent in the literature is the idea that companies must be transparent, honest, and responsive in their communication and community engagement if they are to have any hope of gaining and keeping social license.…”
Section: Social Licensementioning
confidence: 99%
“…The unstructured big data of social media offers more penetration considering the voice of more users from a wider geographical region (Nepal et al, 2015), delivers more user views faster and at a lower cost ( Howard, 2020), may include users who are unwilling or unable to participate in structured studies (Casas and Delmelle, 2017;Howard, 2020), and offers a dynamic perspective allowing temporal evaluation (Collins et al, 2013;Hosseini et al, 2018;El-Diraby et al, 2019). Due to these advantages, social media tools are widely used in developing transport policies (Nepal et al, 2015;Grant-Muller et al, 2015;Casas and Delmelle, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A brief literature review shows that social media is seen as an important communication tool and contributes to the improvement of customer engagement in the transport industry by creating space for passengers to share their opinions and comments (Saragih and Girsang, 2017;Howard, 2020). Social media helps to detect the problem quickly and to reach secure information for passengers with real-time information ow during planned and unplanned disruptions (Pender et al, 2014; Cottrill et al, 2017).…”
mentioning
confidence: 99%